A comprehensive analysis of the factor structure of the Beck Depression Inventory-II in a sample of outpatients with adjustment disorder and depressive episode. (24th October 2017) - McElroy, E.; Casey, P.; Adamson, G.; Filippopoulos, P.; Shevlin, M.
Abstract : Objectives: Despite being commonly used in research and clinical practice, the evidence regarding the factor structure of the Beck Depression Inventory-II (BDI-II) remains equivocal and this has implications on how the scale scores should be aggregated. Researchers continue to debate whether the BDI-II is best viewed as a unidimensional scale, or whether specific subscales have utility. The present study sought to test a comprehensive range of competing factor analytic models of the BDI-II, including traditional non-hierarchical multidimensional models and confirmatory bifactor models. Method: Participants (n=370) were clinical outpatients diagnosed with either depressive episode or adjustment disorder. Confirmatory factor analysis and confirmatory bifactor modelling were used to test 15 competing models. The unidimensionality of the best fitting model was assessed using three strength indices (explained common variance, percentage of uncontaminated correlations and ω hierarchical). Results: Overall, bifactor solutions provided superior fit than both unidimensional and non-hierarchical multidimensional models. The best fitting model consisted of a general depression factor and three specific factors: cognitive, somatic and affective. High factor loadings and strength indices for the general depression factor supported the view that the BDI-II measures a single latent construct. Conclusions: The BDI-II should primarily be viewed as a unidimensional scale, and should be scored as such. Although it is not recommended that scores on individual subscales are used in isolation, they may prove useful in clinical assessment and/or treatment planning if used in conjunction with total scores.